The Maya - Spilsbury, Louise (Spilsbury, Louise. Analyze the ancients., 2019)
Briefly explores the ancient Maya people, covering their city-states, evidence for their advanced technology, their culture and religion, their government, and how they relaxed and played games. Includes a glossary.